DESIGN AND BUILD AN INVENTORY CONTROL ANALYSIS APPLICATION SYSTEM USING THE ECONOMIC ORDER QUANTITY (EOQ) METHOD IN UD. JASMINE JAYA STARTUP-BASED - Khairunnisa Almadany; Rizaldy Khair (Sean Institute, 2022)
Ud. Melati Jaya is a Small and Medium Enterprise (UKM) engaged in processing ja-gung into animal feed. So far, the method of estimating raw material inventory has been UD's choice. Melati Jaya in the procurement of supplies, with the finished goods system has been ordered in advance by consumers so that there is no accumulation of finished goods in warehouses or pre-order systems, but in the process of fulfilling raw material inventories there are often delays due to shortages of raw materials in the market. This hampers the production process and if it occurs continuously will increase the chances of UD losses. Jasmine Jaya. In previous studies, it can be explained that the results of calculations in reducing UD inventory costs. Melati Jaya, specifically with a January demand supply of 73,993 kg, can be minimized with an optimal purchase of 16,058 kg with a frequency of 5 purchases per month and a safe supply of 2,963 kg. and place an order again when the quantity reaches 8,650 kg. The inventory cost that can be saved is Rp.17,504,704 using the EOQ (Economic Order Quantity) method which is a technique for procuring raw material inventory at a company according to the number of orders. But in the bookkeeping records of UD. Melati Jaya from February to March 2020 is still not good so there are some transactions that are not recorded properly, so the calculation results in that month are inefficient [1]. The purpose of this study is to find out how to control inventory using the collaboration of the EOQ and RAD (Rapid Application Develop-ment) methods as a technology implementation that will make it easier to analyze inventory in real time. The data analysis method used is a quantitative descriptive method. The data obtained from the measurement results can be used as an analysis of the next program situation by using test analysis using SPSS on the running system and turning it into an automation and realtime system. This Application System is built using the PHP programming language, and the CodeIgniter framework and uses a MySQL database server.